Analysis of Financial Statements - Comparative Study of Pediatric Hospitals of the 1st Regional Health Authority, during the period 2010-2021 - Vernadakis, Michail; Roupas, Theodoros (International Conference on Business and Economics - Hellenic Open University, 2025)
In the period 2010-2021, Greece faced a challenging period, having to cope with numerous economic problems (due to the financial crisis) and in managing health care challenges posed by the coronavirus (due to the COVID-19 pandemic). The negative effects of the economic crisis prompted the government to introduce strict austerity measures, which led to a reduction in public spending and funding. The healthcare sector was also affected, as healthcare facilities were confronted with various new challenges that made proper management of existing resources essential. Therefore, improving the efficiency of hospitals became an essential prerequisite for their smooth operation and the continuous provision of high-quality healthcare services. Analyzing financial data from a healthcare facility's financial statements, examining its efficiency (using financial ratios and trend indicators) along with analysis of their expenses, are methods that can help overcome the challenges preventing its economic growth and sustainability. In this context, through the financial analysis of the financial statements of the Pediatric hospitals of the 1st Regional Health Authority and specifically the General Pediatric Hospital (G.P.H.) "Panagiotis & Aglaia Kyriakou", the General Pediatric Hospital "Agia Sofia" and the General Pediatric Hospital of "Pentelis" for the years 2010-2021, the present study aims to examine if the economic and pandemic crisis affected their financial efficiency, activity, liquidity and capital structure and to determine the extent of this impact. JEL Classifications: G34, G14, M41 Keywords: COVID-19 Pandemic, Economic Crisis, Financial Analysis, Healthcare Efficiency, Pediatric Hospitals